Urgency of Field of Accounting in The Era of Artificial Intelligence - Sudarman, Sudarman (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2025)
Objective: to study the impact of artificial intelligence in accounting, how to respond, and the need for future research development. Method: The main data source is 321 scientific articles, to study conceptually, using the PRISMA method, 33 selected articles were obtained, and the analysis was carried out using a systematic literature review. Results: RQ1, conceptually, the implementation of artificial intelligence has an impact on anticipating fraud, accounting information systems, financial and management accounting, and the accounting profession. The quantitative approach proves that artificial intelligence has a significant impact on the performance of accounting functions, accountability and transparency of financial reports and data privacy. RQ2, accountants must have new readiness and skills. RQ3, future research must consider primary data, samples, quantitative designs, variables, and objects. Renewability: that information technology readiness has an impact on the adoption of artificial intelligence both directly and through mediators of perception and ease of use. Future Research Agenda: to test hypotheses based on this novelty.